Transforming Student Literacy in the Digital Era: The Effect of Discovery-Based Reading with Leveled Books on Critical Reading Comprehension - Kiranti, Nandia; Yuniarti, Yeni (International Conference on Elementary Education, 2025)
This research was motivated by the low level of critical reading comprehension skills among elementary school students, which reflects one of the indicators of low reading literacy in Indonesia as reported by the 2022 PISA study. Reading instruction in schools generally focuses more on reading fluency rather than on text comprehension. Therefore, it is necessary to apply learning methods that can enhance students’ critical thinking and reading comprehension skills, one of which is the discovery based reading (DbR) method supported by digital leveled books. The purpose of this study was to analyze the effect of the discovery based reading method on elementary school students’ critical reading comprehension skills and to compare it with the SQ3R method. The study employed a quasi experimental design using the Matching-Only Pre-test-Post-test Control Group Design. The research subjects consisted of 43 fifth-grade students from two elementary schools in Bandung Regency, divided into experimental and control groups. Data were collected through a critical reading comprehension test covering six critical thinking indicators and analyzed using normality, homogeneity, and t-test statistical tests to examine the hypotheses. The results showed a significant improvement in critical reading comprehension skills for both the experimental class using the discovery based reading method and thecontrol class using the SQ3R method. The average post-test score of the experimental class increased from 52.08 to 88.75, while that of the control class increased from 37.40 to 76.90. However, the gain test results indicated no significant difference between the two methods. In conclusion, both discovery based reading and SQ3R methods are effective in improving students’ critical reading comprehension skills. These methods can complement each other and be applied flexibly in Indonesian language learning to enhance students’ literacy and critical thinking skills in the digital era.